If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -1) + -3(x + 1) = 2(x + -4) Reorder the terms: 4(-1 + x) + -3(x + 1) = 2(x + -4) (-1 * 4 + x * 4) + -3(x + 1) = 2(x + -4) (-4 + 4x) + -3(x + 1) = 2(x + -4) Reorder the terms: -4 + 4x + -3(1 + x) = 2(x + -4) -4 + 4x + (1 * -3 + x * -3) = 2(x + -4) -4 + 4x + (-3 + -3x) = 2(x + -4) Reorder the terms: -4 + -3 + 4x + -3x = 2(x + -4) Combine like terms: -4 + -3 = -7 -7 + 4x + -3x = 2(x + -4) Combine like terms: 4x + -3x = 1x -7 + 1x = 2(x + -4) Reorder the terms: -7 + 1x = 2(-4 + x) -7 + 1x = (-4 * 2 + x * 2) -7 + 1x = (-8 + 2x) Solving -7 + 1x = -8 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -7 + 1x + -2x = -8 + 2x + -2x Combine like terms: 1x + -2x = -1x -7 + -1x = -8 + 2x + -2x Combine like terms: 2x + -2x = 0 -7 + -1x = -8 + 0 -7 + -1x = -8 Add '7' to each side of the equation. -7 + 7 + -1x = -8 + 7 Combine like terms: -7 + 7 = 0 0 + -1x = -8 + 7 -1x = -8 + 7 Combine like terms: -8 + 7 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1
| 5(x+30)=2(x+6) | | 5(2y+3)-3(4y-1)=12 | | 5x-5=70+x | | 2(2x+1)-3(2x-1)=-3 | | 4(x+2)-5(x-3)=24 | | 3(x+5)-2(x-1)=19 | | 2(y+5)-(y+4)=8 | | 5(x+2)-3(x+1)=9 | | 2-4x=1-5x | | 5-3t=7-t | | 5x+12=-27+8x | | 3+2x=18-3x | | 10-2x=4+x | | 3a-1=7a-9 | | 3x+12=58-2x | | 9a=a+16 | | 5x-4y=19y | | k(x^2-3x+4)+x-3=0 | | f(4x^2+3)=0 | | k^2-k-2=0 | | 7(5-x)=14 | | k^3-k^2-2k-12=0 | | (x-3)(x^3-1)=0 | | x^8=-1 | | 111-5x=13x+23 | | 147-6x=21x+21 | | 4(h*h)+5h=84 | | 6z-12=5 | | 10x-22+5x=3 | | (78).425= | | 5x=3x^2 | | (5x+3)*(24-3x)=0 |